Legal, Marketing, and Advertising Issues with Big Data - Donald L. Buresh (Journal of Big Data Research, 2022)
The purpose of this essay is to discuss the advantages and disadvantages and the benefits and costs of Big Data. The paper outlines the relevant federal and state privacy laws, including the California Consumer Privacy Act as amended, the Virginia Consumer Data Protection Act, and the Colorado Privacy Act. While highlighting several Federal Trade Commission privacy violation cases, the effects of Big Data collection and government surveillance are described in some detail. Advertising and marketing are defined, where it is argued that while the scanning of emails by email providers may be legal, it should be accomplished with consent, or not at all. The essentials of contract law and specific contract negotiation techniques are outlined for the benefit of attorneys. Finally, it is argued that although Big Data is the wave of the future, like all human institutions, it has in its definition the inherent paradoxes of transparency, identity, power, and exclusion that may potentially spell its undoing.
Keywords: Big Data